Clinical safety, tolerability, pharmacokinetics and effects on urinary electrolyte excretion of AZD9977, a novel, selective mineralocorticoid receptor modulator. (22nd April 2018) - Erlandsson, Fredrik; Albayaty, Muna; Chialda, Ligia; Ericsson, Hans; Amilon, Carl; Nelander, Karin; Jansson‐Löfmark, Rasmus; Wernevik, Linda; Kjaer, Magnus; Bamberg, Krister; Hartleib‐Geschwindner, Judith
Abstract : Aims: AZD9977 is the first mineralocorticoid receptor modulator in clinical development exerting similar organ protection as eplerenone with minimal urinary electrolyte effects in preclinical studies. The aim was to perform the initial clinical assessment of AZD9977. Methods: A first‐in‐human trial explored doses from 5 to 1200 mg. To study effects on urinary electrolyte excretion an additional randomized placebo controlled cross‐over four‐period clinical trial was performed. Twenty‐three healthy volunteers were administered fludrocortisone alone or in combination with AZD9977, eplerenone or both. AZD9977/eplerenone combination was given to assess if AZD9977 can attenuate eplerenone induced natriuresis. Results: AZD9977 at doses from 5 to 1200 mg was safe and well tolerated and pharmacokinetics were compatible with further development. AZD9977 exhibited similar effects on urinary ln [Na + ]/[K + ] as eplerenone when using fludrocortisone as mineralocorticoid receptor agonist, and the combination had an additive effect on ln [Na + K + ]. Conclusions: The results in man contradict the results in rodent models driven by aldosterone, in which AZD9977 has minimal electrolyte effects. Future clinical studies with AZD9977 should be performed in presence of endogenous or exogenous aldosterone to assess potential benefit of AZD9977 in patients.